Towards mid-infrared fibre lasing - Nunes, Joel (2024)
This thesis focused on the development of trivalent lanthanide doped chalcogenide glasses intended for the fabrication of MIR (mid-infrared) fibre lasers operating at wavelengths beyond 4 μm. The fabrication and spectroscopic evaluation of separate trivalent ‘Ce’ (cerium), ‘Pr’ (praseodymium), ‘Sm’ (samarium), ‘Tb’ (terbium), and ‘Dy’ (dysprosium) cation doped chalcogenide glass samples was undertaken as the first step towards achieving this goal. These RE3+ (rare-earth) doped chalcogenide glass samples were produced using the ‘melt/quench’ technique, then drawn into single material fibres (fibre without a glass cladding) and/or fabricated into a SIF (step-index fibre) using the ‘rod-in-tube’ technique. Emerging from the production and fabrication of these RE3+ doped samples was a novel non-destructive evaluation technique using either NIR or MIR imaging to detect internal defects and inhomogeneities in glass samples. As a result of this work the capability to produce RE3+ doped bulk chalcogenide glass, single material fibre SIF and extruded glass rods and tubes was demonstrated with some RE3+ doped glass compositions exhibiting optical losses as low as 1.81 ± 0.29 dB/m. Additionally, the ability to cause permanent photoinduced refractive-index changes in RE3+ doped glass was also demonstrated. There was also evidence of defects within several chalcogenide glass samples during their production and fabrication, alluding to room for improvement in the employed methodology.